Proceedings of the 3rd International Conference on Education and Training (ICET 2017) 2017
DOI: 10.2991/icet-17.2017.10
|View full text |Cite
|
Sign up to set email alerts
|

A Literature Review of Indonesian Life Concept Linuwih Based on the Teachings of Adiluhung Raden Mas Panji Sosrokartono

Abstract: Abstrack:The linuwih counseling study is based on the importance of the counselor to understand the noble values and meaningfulness of the counselee's life. Counselor's understanding of the counselee's life is passed on as counselor's expertise to creater the potential resources of the counselee as a manifestation of a more meaningful quality of life through sophisticated efforts based on cultural understanding of the counselee. The principles of Raden Mas Panji Sosrokartono that are formulated in pockets of s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0
4

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 13 publications
(5 reference statements)
0
5
0
4
Order By: Relevance
“…Habsy et al [25] indicated that the implementation of counselling services in Indonesia is oriented to the counselling from Western countries; that is, matters pertaining to good counselling techniques, procedures and stages are adopted from counselling from the West. In terms of development in the paradigm of counselling, there has been a shift so that thinking concerning the typical indigenous counselling of Indonesia has started to develop.…”
Section: Introductionmentioning
confidence: 99%
“…Habsy et al [25] indicated that the implementation of counselling services in Indonesia is oriented to the counselling from Western countries; that is, matters pertaining to good counselling techniques, procedures and stages are adopted from counselling from the West. In terms of development in the paradigm of counselling, there has been a shift so that thinking concerning the typical indigenous counselling of Indonesia has started to develop.…”
Section: Introductionmentioning
confidence: 99%
“…Konselor Indonesia perlu mengembangkan kesadaran diri mereka sendiri tentang sifat manusia Indonesia dengan tidak meminjam "pakaian" konseling Barat. Konselor dituntut memiliki kepekaan budaya dan kemampuan untuk melepaskan diri dari bias budaya (All Habsy et al, 2017).…”
Section: Hasilunclassified
“…Desain atau rancangan penelitian merupakan suatu proses yang diperlukan dalam perencanaan dan pelaksanaan sebuah penelitian (Habsy, Hidayah, Lasan, & Muslihati, 2017). Jenis penelitian yang dipakai oleh peneliti dalam penelitian ini adalah penelitian kuantitatif, yang merupakan jenis penelitian utama untuk mengetahui keefektifan konseling Behavior untuk meningkatkan manajemen diri siswa, maka penelitian ini termasuk penelitian eksperimen.…”
Section: Metode Penelitianunclassified